Terahertz spectroscopy for analysis of vaterite-to-calcite crystal phase transition induced by distilled water - Shuhei Okada; Naoya Kurahashi; Yukihiro Tanida (PLoS ONE, 2025)
Vaterite is a crystalline polymorph of anhydrous calcium carbonate (CaCO3), which exhibits relatively low stability compared to other two polymorphs, calcite and aragonite. Vaterite particles have properties such as large specific surface area, high porosity, and high solubility; hence, research has been made in wide range of applications from material additive to drug delivery. X-ray diffractometry (XRD) is capable of identifying polymorphs of calcium carbonate. However, depending on the base material and the installed state, it may not always be suitable for non-destructive observation. This study reveals that vaterite-to-calcite crystal phase transition degree can be quantified by the absorption spectrum in terahertz range. The vaterite concentration and the terahertz absorption peak intensity near 3.3 THz showed linearity with correlation coefficient of R2 = 0.934 in our experiment. The findings allow us to quantitatively evaluate vaterite-to-calcite crystal phase transition in non-destructive and non-invasive way.